Financial statement analysis: a review and current issues. Issue 1 (7th December 2021) - Jackson, Andrew B.
Abstract : Purpose: The literature on financial statement analysis attempts to improve fundamental analysis and to identify market inefficiencies with respect to financial statement information. Design/methodology/approach: In this paper, the author reviews the extant research on financial statement analysis. Findings: The author then provides some preliminary evidence using Chinese data and offer suggestions for future research, with a focus on utilising unique features of the Chinese business environment as motivation. Originality/value: The author notes that there has been no work that the author could locate specifically on Chinese FSA research. The unique business environment in China, relative to the US where the vast majority of this work has been conducted, should motivate any studies, especially given the author documents the robust finding in terms of the mean reversion in profitability.